Legal Review of Unlawful Acts in Internet Purchase Transactions (E-Commerce) Based on the Civil Code - Datau, Rahmat (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
The advancement of information technology has significantly transformed the structure of community activities, particularly in the trade sector. Many individuals engaged in sales now utilize digital platforms for marketing, making the process more efficient and profitable. Traditional physical shops are gradually being replaced by online commerce. However, this rapid development also brings challenges, particularly in the form of unlawful acts that may harm other parties. Therefore, a legal solution is necessary to address, prosecute, and enforce the law in the electronic commerce sector. This is essential to ensure legal certainty for business actors and to resolve legal violations fairly and systematically. The background of this study refers to several legal frameworks, namely Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE), the Civil Code (KUHP), and Law Number 8 of 1999 concerning Consumer Protection. This research aims to serve as a valuable reference for the public to actively participate in e-commerce with a clear understanding of their rights and obligations. Furthermore, the study is expected to assist law enforcers in preventing, handling, and taking legal action against civil law violations by digital business actors. The results highlight the ongoing need for systematic efforts to educate the public comprehensively about e-commerce transactions and their legal protection through relevant laws, especially the UU ITE, KUHP, and Consumer Protection Law.